Luxury fashion and sustainability: looking good together. Issue 4 (20th August 2019) - Campos Franco, Jacqueline; Hussain, Dildar; McColl, Rod
Abstract : Purpose: The purpose of this paper is to highlight critical sustainability challenges facing luxury fashion firms and to describe examples of best practice in responding to these challenges. Design/methodology/approach: The research approach combines a detailed literature review with multiple-case examples. The paper adopts the triple bottom line framework for structuring the analysis and findings, which suggests reporting sustainability efforts in three categories of actions – social, environmental and economic. Findings: Prior research suggests that luxury fashion marketing and principles of sustainability may represent contradictory philosophies. However, this paper of case examples suggests that this may no longer be the case. We identify six lessons in guiding future sustainability practices. Practical implications: The findings have implications for managers operating in luxury fashion, but the findings are also pertinent to managers in other industries. Originality/value: Prior research in luxury fashion has generally focused on the industry's poor record in sustainability and how luxury and sustainability may be incompatible. In this paper, we conclude that most luxury fashion firms are aware of the need to integrate sustainability into their business models. By uncovering examples of best practice in sustainability, we demonstrate how luxury fashion firms have responded to these challenges with lessons for other industry sectors.